Insights from SONATA: Implementing and integrating a microservice-based NFV service platform with a DevOps methodology - Soenen, Thomas; Van Rossem, Steven; Tavernier, Wouter; Vicens, Felipe; Valocchi, Dario; Trakadas, Panos; Karkazis, Panos; Xilouris, George; Eardley, Philip; Kolometsos, Stavros; Kourtis, Michail-Alexandros; Guija, Daniel; et al. (NOMS 2018 - 2018 IEEE/IFIP Network Operations and Management Symposium, 2018)
In pursuit of a flexible, resource efficient and high- performant 5G infrastructure, many operators, vendors and research consortia are currently developing, testing and integrating their NFV platform with associated management and orchestration (MANO) functionality. The SONATA NFV platform follows a micro-service design, which involves a tight coupling between an SDK, monitoring and MANO functionality, targeting a secure and stable software foundation. This experience paper gives a thorough overview on the encountered challenges, insights and resulting learnings when implementing and integrating the SONATA Service Platform using a continuous integration and delivery DevOps methodology. This is the result of a strong cooperation between prominent equipment vendors, network operators, software companies and universities, providing a set of constructive recommendations in hope of catalysing the development and deployment of NFV platforms.